UiTM Prospectus 2000/2001 / Pejabat Perhubungan Korporat, UiTM - Pejabat Perhubungan Korporat, UiTM (Pejabat Perhubungan Korporat, UiTM, 2000)
UiTM is the first public institution of higher learning in Malaysia to be awarded the ISO 9002 certificate. It won the Public Service Quality Award in 1996. UiTM also received the Tun Razak Award for having successfully uplifted the quality of life of the poor and at the same time producing Bumiputera graduates and entrepreneurs.